Mineral occurrence in vegetarian foods - Santiago, Susana (2022)
Calcium, iron and zinc are minerals of greatest concern when considering the nutritional value of vegetarian diets, since those minerals are mostly present in animal foods. Aim: The aim of this study was to assess calcium, iron and zinc contents in vegetarian foods.